JUMPA Vol.2 No.3 Okt 2015 DAMPAK STRES KERJA DAN TINGKAT KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN OTOMOTIF: DAMPAK STRES KERJA DAN TINGKAT KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN OTOMOTIF - Riyan Saputri Sekolah Tinggi Ilmu Ekonomi Y.A.I; Noviherni Noviherni (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
Studied in this thesis is the impact of job stress and job satisfaction on the performance of employees at Automotive Company in East Jakarta. Job Stress is the independent variable (X1) and job satisfaction (X2) while the dependent variable is Employee Performance (Y). The purpose of this study was to determine the effect of job stress and job satisfaction on employee performance in East Jakarta Automotive Company. In this study, the object is the marketing division employees Automobile Company in East Jakarta. Data collection techniques used in this research that the author conducted field research by distributing questionnaires to employees. This study respondents totaled 92 people. Based on the research results that: The relationship of job stress with the negative performance of the employees is very low and where the value of r = -0127 Y = 40.291-.077 X1, while the t test results showed tcount <ttable or -0.1225 <1.987 then Ha is accepted and Ho is rejected it means there is influence between work stress with employee performance. The relationship between job satisfaction and employee performance is very strong and positive where r = 0.817 with a value of Y = 22.621 + 0.358 X2. While the test results show tcount > ttable or 23.343> 1.987 then Ho is rejected and Ha accepted meaning there is influence between job satisfaction on employee performance. The relationship between job stress and job satisfaction on employee performance is strong and positive where r = 0.668 with a value of Y = 22.822-0.014 X1 + 0, 365X2 while the F test results indicate Fcount > Ftable or 6.635 > 3.099 then Ha Ho accepted and rejected, meaning there are significant job stress and job satisfaction on employee performance.